The Importance of Automatic Counters for Sustainable Management in Rural Areas: The Case of Hiking Trails in Historic Villages of Portugal - Ana Luque; Luiz Alves (Land)
The dynamics of territorial planning, the management of its tourism products, and the monitoring of demand flows and their impact on the territorial structure (social, economic and environmental) require tools that support the acquisition of reliable quantitative data, as far as possible in real time, that are easy to manage and allow immediate analysis. In the case of structures and equipment anchored in the nature tourism segment, in particular hiking trails, in addition to determining the demand indices in a network of hiking trails and understanding their territorial and temporal dynamics, the data collected through automatic counters is a crucial tool to support territorial management and evaluate the patterns and flows of tourist demand. Based on these assumptions, this research seeks to analyse demand data observed on eleven hiking trails in the Historic Villages of Portugal, collected through automatic monitoring systems (counters). In four years, between 2020 and 2023, the trails analysed generated a demand of almost 190,000 passages, which translates into an annual average of 47,500 passages in the tourism product “Historic Villages of Portugal” (more than 4800 passages for each trail), mostly in the spring and autumn months, mainly on weekends.